Total ankle replacement with antibiotic-impregnated cement: a case report on the infected ankle management - Reyanne N. Strong; Abigail E. Smith; Nathaniel T. Koutlas; James O. Sanders; Trapper Lalli (Journal of the Foot & Ankle)
Ankle fracture infection is a devastating complication that can lead to chronic pain, limited motion, post-infectious end-stage ankle arthritis, osteomyelitis, and amputation. Treatment historically involves aggressive debridement, hardware removal, and long-term antibiotic therapy. We describe a case of post-infectious end-stage ankle arthritis treated with a custom, fixed-bearing, 3D printed total ankle replacement with antibiotic-impregnated cement. The provided treatment allows continued elution of high-dose local antibiotics while preserving the ankle range of motion and allowing immediate weight bearing postoperatively. Level of evidence V; Therapeutic studies; Expert opinion.